Chemical and nutritional properties of different fractions of Prosopis alba pods and seeds - Sciammaro, Leonardo Pablo (2016)
The objective of this work was to study chemical and nutritional aspects of different fractions of Prosopis alba. Flours from whole pod, pericarp (pulp) and seeds were obtained. Polyphenols were mainly located in pulp but antioxidant activity was higher in whole pod flour and seeds. In seeds, the fraction with the highest polyphenols and antioxidant activity was the seed coat or testa. Protein content was higher in whole pod flour (5.81 %) than in pulp flour (3.52 %), presenting the seed an appreciable amount 33.6 %. These proteins were composed by monomer subunits of 85, 67, 38, 16 and 14 kDa and no prolamins and anti-tryptic activity were detected. P. alba flours presented high content of soluble sugars, mainly composed by sucrose, and also high amount of insoluble dietary fiber. The major mineral was potassium. The whole pod, due to the contribution of seeds, contained high amount of calcium, magnesium, iron and zinc, all indispensable minerals for human nutrition. Therefore, P. alba flours, mainly containing the seeds, constitute nutritional ingredients for bakery and gluten free products.